Model of the Initial Stage of Bioactive Coating Deposition; AIP Conference Proceedings; Vol. 2051 : Advanced Materials with Hierarchical Structure for New Technologies and Reliable Structures 2018 (AMHS’18) - Nazarenko N. N. (2018, 2018)
Title screen